Giant hepatic hemangioma in a patient with cirrhosis: challenging to manage - Cunha-Silva, Marlone; Veiga, Clauber Teles; Costa, Larissa Bastos Eloy da; Perales, Simone Reges; Furlan, Amanda Avesani Cavotto; Ataíde, Elaine Cristina de; Boin, Ilka de Fátima Santana Ferreira; Sevá-Pereira, Tiago (Autopsy and Case Reports, 2024)
Giant hepatic hemangiomas are occasional in patients with cirrhosis. It remains a challenge to decide on the need for treatment and choose the most appropriate intervention. A 62-year-old woman was recently diagnosed with cirrhosis and complained of upper abdominal fullness, reduction in oral food intake, and weight loss of 6 kg over the last three years. Upper digestive endoscopy evidenced thin-caliber esophageal varices and significant extrinsic compression of the lesser gastric curvature. Abdominal computed tomography revealed an exophytic tumor in the left hepatic lobe, measuring 11.5 cm, which had progressive centripetal contrast enhancement from the arterial phase, compatible with hepatic hemangioma. Serum tumor markers were negative, and her liver function was unimpaired. The patient underwent surgical resection (non-anatomical hepatectomy of segments II and III) which had no immediate complications, and the histopathological evaluation confirmed cavernous hepatic hemangioma. Two weeks later, she was admitted to the emergency room with jaundice, signs of hepatic encephalopathy, and moderate ascites, and was further diagnosed with secondary bacterial peritonitis. As no perforations, abscesses, or fistulas were observed on subsequent imaging tests, clinical management was successfully carried out. This case highlights that giant hepatic hemangiomas may be symptomatic and warrant treatment. In the setting of cirrhosis and portal hypertension, physicians should be aware of the risk of hepatic decompensation following surgical resection, even in patients with Child-Pugh class A.